Exploration of hidden Pb–Zn–Cu–Au mineralization by geophysical methods (IP, resistivity, SP): a case study in Kirazoren mineralization, NE Turkey - Tezel, Okan; Üge, Mehmet Ali (Geosciences journal (Seoul, Korea), 2025)
In this study, we aimed to determine the possible locations and the depths of the Middle Black Sea region vein-type of Zn–Pb ± Cu deposits located in Kirazoren, Giresun, Turkey, by using geophysical methods. We conducted this study to investigate and locate the ore trace lost due to a fault in the gallery driven during ore production. Due to the highly rugged terrain and dense vegetation cover of the study area, core samples could not be taken, necessitating this study by investigating it with the geophysical methods. We applied the geophysical methods such as vertical electrical sounding, resistivity, time-domain induced polarization, self-potential, and electrical resistivity tomography, all together. At the measurement points determined in line with the geological information obtained from the driven gallery, the geophysical data were acquired. By comparing these geophysical data with geological information of the study area, the possible location and the depth of the ore vein was identified. Additionally, to prove the results and to determine the possible underground condition of the ore, electrical resistivity tomography method was applied on the identified ore location. The interpretation of the geophysical data, by considering the geological field observations and structural disturbances, revealed that high-value chargeability (125 ms), low-value resistivity (287 Ω m), and low-value self-potential (− 100 mV). The interpretation results were consistent with the old driven galleries and the geology of the study area. Consequently, it was successfully obtained that applying and interpreting four geophysical methods simultaneously can lead to positive results in exploring covered or deep-seated ores, even in the areas where the topography and vegetation do not allow for core sampling and outcropping.